Coordinated Control Strategy of Short-Turning Bus and Full-Length Bus Based on Stable Headway - Huasheng Liu; Yu Li; Yanqiu Zhang; Jin Li; Yi Wang (Discrete Dynamics in Nature and Society, 2022)
Under the condition of dynamically collecting vehicle operation information, bus dynamic dispatching is an effective means to stabilize the vehicle operation according to the traffic plan and improve the stability of the system by giving real-time response and continuous dynamic control to the vehicle running state. Speed control does not increase the extra parking time at the station, does not waste parking resources, does not significantly prolong the waiting time of passengers at the station, and is more easily accepted by passengers. In this paper, by using the speed control method, the problem of how to realize the coordinated control between the short-turning bus and the full-length bus is studied in order to stabilize that the headway between the full-length buses is equal to the departure interval, and the headway between the short-turning bus and the full-length bus is equal to the expected headway. The problem of ensuring the coordinated and stable operation of the short-turning bus and the full-length bus is studied. The result of an example shows that the coordinated control strategy can make the whole system run more stable.